Adenosine A2A receptors in the rat hippocampus: stress related changes - Batalha, Vânia Luísa Neves (2011)
Tese de mestrado, Bioquímica (Bioquímica Médica), Universidade de Lisboa, Faculdade de Ciências, 2009